Natural Disasters in the Metropolitan Region of Belo Horizonte: A Summary of Events Occurred in the Rainfall Period of 2019/2020 - Silva, Denise de Fátima Santos da; Parisi, Maria Giovana; Silva, Elaine Aparecida Santos da; Silva, Guilherme Andrade Ranier (Anuário do Instituto de Geociências, 2023)
This article presents a summary and analysis of the consequences on the latest disasters that occurred in Minas Gerais, especially in the Metropolitan Region of Belo Horizonte (RMBH). The databases used in this study were the bulletins from the main bodies that manage water resources and natural disasters in the state of Minas Gerais, such as Civil Defense, CEMADEN, IGAM and CEPEDUFSC. It is worth mentioning that the cities of Belo Horizonte, Ibirité and Florestal were the holders of pluviometry records in the rainy period of 2019/2020 and therefore, carry the largest numbers with regard to material damage (Ibirité) and the deaths (Belo Horizonte). Nevertheless, it is important to highlight the significant number of injured, sick and homeless people due to the bad weather in Contagem. It is known that the RMBH has a vast history of events related to natural disasters and bottlenecks regarding urban planning. Therefore, the identification of these risk areas is a very important tool for mapping vulnerable locations and drawing concrete action plans aimed at neutralizing events, strengthening the city’s urban infrastructure and mainly preserving lives.